Implementation of Smart Governance in Realizing Tomohon Smart City - Marthinus M. Mandagi; Jeane Mantiri; Sisca B. Kairupan (Indonesian Association for Public Administration (IAPA), 2020)
This study aims to describe the implementation of smart governance in realizing Tomohon Smart City. This study used a qualitative approach, with data collection techniques, namely interviews, observation and documentation. Sources of data from informants are: Head of Tomohon City E-Government Administration, Tomohon City Technology and Communication Infrastructure Section Head, Tomohon City Application Development Section Head, Tomohon City Communication and Informatics Office Staff / Staff, Matani Village Head, and Tomohon City community as users infrastructure and facilities provided by the government. Data analysis using data reduction, data presentation, and drawing conclusions. Data were analyzed descriptively qualitatively. The results showed that: 1) The rules governing the running of the program or policy have not been well socialized and communicated, especially in agencies that have a role as implementers. 2) The government, in this case the Tomohon City Information and Communication Service, is still closed in providing information related to Smart City, especially Smart Governance. 3) The government has not yet launched a public complaint application even though it has been launched since 4) The government is still not ready to respond to existing technological and social developments, especially in the process of implementing Smart Governance. The Conditional Factors of Policy Implementation are a) Information Distribution, b) Resource Support, c) Government Attitude, d) Implementers. Therefore, it can be suggested, 1) There is a need for better socialization, communication and coordination regarding existing regulations to members and related agencies. 2) The government must be more open to the public, and must better prepare itself in responding to all situations and conditions that exist, especially in running the Tomohon Smart City program. 3) The government must improve work discipline, especially in the recruitment process, in order to create